Intrinsic immunosuppressive features of monocytes suppress CAR-T19 through IL-1 pathway modulation in mantle cell lymphoma - Kun Yun; R. Leo Sakemura; Ismail Can; Omar Gutierrez Ruiz; Ekene J. Ogbodo; Shuwen Zhang; Ateka Saleh; Truc N. Huynh; Claudia Manriquez Roman; Olivia L. Sirpilla; Carli M. Stewart; James H. Girsch; et al. (Molecular Therapy: Oncology)
CD19-targeted chimeric antigen receptor T cells (CAR-T19) have shown remarkable success in B cell malignancies, but most patients relapse within 1–2 years. Here, we identified interleukin-1 (IL-1) receptor antagonist (IL-1ra) as a mediator of M2-like macrophage-derived inhibition of CAR-T19 in mantle cell lymphoma (MCL), as well as a potential target to enhance CAR-T19 efficacy. In preclinical models that recapitulated interactions between tumor, macrophages, and T cells, we demonstrated that M2-derived IL-1ra impairs IL-1 signaling and functions of CAR-T19. These findings were validated using clinical samples from the ZUMA-2 trial that led to the FDA approval of CAR-T19 in MCL. Single-cell RNA sequencing of CAR-T19 products and baseline myeloid cells indicated downregulated IL-1β production, enriched immunosuppressive phenotypes, and IL-1ra upregulation in the non-responder monocytes, as well as impaired IL-1β signaling and T cell functions in the non-responder CAR-T19 products. Furthermore, our preclinical studies of IL-1β showed enhanced CAR-T antitumor activities. Collectively, these data present a potential role for IL-1 signaling and IL-1ra in CAR-T19 failure.